Health-Seeking Behavior of Diabetic and Hypertensive Patients in Rural Communities of Ghana - Michael Amponsah Kodom (Pan-African Journal of Health and Environmental Science)
Background: This study examined the health-seeking behaviors of patients with diabetes and hypertension in rural communities in Ghana. In Ghana, most studies on diabetes and hypertension are clinically oriented. However, medical-sociological truism suggests that attitudes towards health and illnesses, such as hypertension and diabetes, have a social-cultural perspective.